Bulgaria : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2016)
This paper highlights Bulgaria's state-owned enterprises (SOEs) sector and to assess its performance in a regional perspective. A detailed and rich firm-level dataset of state-owned and private firms was compiled for this note to compare key performance indicators of SOEs to private firms in the same sector and to similar firms in Croatia and Romania for a regional comparison. In some network industries, such as energy, SOEs are heavily loss-making. Large amounts of debt have been piled up notably in the energy and transport sectors which, to the extent that it is classified outside the general government accounts, can pose significant risk to public finances in the form of contingent liabilities if the SOEs run into financial difficulties. SOE profitability and resource allocation efficiency largely lag private firms in the same sectors, even when isolating SOEs engaged in competitive market activities and hence classified outside of general government. Coupled with comparably poor output quality, these challenges have the potential to impair competitiveness and productivity across the economy.